Who's who in fashion - Alford, Holly Price; Stegemeyer, Anne (Fairchild Books, an imprint of Bloomsbury Publishing Inc., 2014)
"Students of fashion design are eager to explore the history of their chosen field as well as keep up with new and emerging designers. Who's Who in Fashion captures the energy, drama, and excitement of the luminaries who make up the world of fashion. Profiles include design philosophies, mentors, and sources of inspiration, tracing the careers of many of the men and women who have contributed to fashion. Not only are today's major figures and legendary designers of the past profiled, but lesser-known individuals and newcomers worth watching are included as well. Also included are the interesting nonconformists--free spirits who prefer to work off the main fashion path. The picture would not be complete without the style-makers, those with an instinct and an eye for fashion, who interpret it for the public: the editors, photographers, and artists"-- Resumé vydavatele
Keywords: 1820-2014; 19.-21. století; módní návrháři -- 19.-21. století; módní návrhářky -- 19.-21. století; módní návrhářství -- 19.-21. století; dějiny módy -- 19.-21. století; fashion designers -- 19th-21st centuries; fashion design -- 19th-21st centuries; history of fashion -- 19th-21st centuries; přehledy; biografické slovníky; surveys; biographical dictionaries